Studies on Neotropical Pseudophyllinae: A new, short-winged Platyphyllini genus (Orthoptera: Tettigoniidae) from a High Andean Forest in Colombia - Cadena-Castañeda, Oscar J.; Medellín-Becerra, Sofía; Molina, Jorge (Zootaxa, 2022)
By combining different research disciplines, biologists can understand natural processes in a broader way. Here, we combine both taxonomic and bioacoustic methodologies to provide the first observations of the morphology, geographical distribution, and the acoustic behavior of the monotypic genus Andeophylloides n. gen. This katydid is the second short-winged genus of the tribe Platyphyllini, after Brachyplatyphylloides, both of which are found in the Colombian Andes. This new genus is unique, because it is the first to be collected in a High Andean Forest, in contrast to the other members of the tribe that have been found predominantly at lower elevations. The sound recordings showed males calling with an echeme duration in average of 5.9 ± 3.1 s, a peak frequency of 22.5 kHz, and peak activity starting at 19:00 and decreasing until 05:00. These calls occur mainly in the months of the first rainy season of the year (March to May). Andeophylloides zarauzensis n. sp., is the sixth species of platyphyllines which calling song is known. Additionally, we discuss the taxonomy, bioacoustics, and differentiate the species with Dasyscelidius atrifrons (Pleminiini). This is required as the females are superficially similar and both species share the same geographical distribution.